2014
DOI: 10.1039/c4ra06043a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical codeposition of graphene platelets and nickel for improved corrosion resistant properties

Abstract: A study on graphene platelet (GPL)/nickel (Ni) composites was carried out to evaluate the potential of the new coating materials for corrosion resistance applications. Electrochemical deposition of Ni and GPL/Ni coatings on mild steel was performed in electrolytes with concentrations of 0, 0.1 and 0.2 g L À1 GPLs.Microstructures of the deposited coatings were examined using X-ray diffraction (XRD) and scanning electron microscopy. A Raman microscope was used to characterize the GPLs in the GPL/Ni composite coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 34 publications
(45 reference statements)
4
46
0
2
Order By: Relevance
“…Some examples include the deposition of GO/chitosan films for drug release [53], CoFe 2 O 4 /rGO, Ni/GO and Sn nanoparticle/rGO films for energy storage [119][120][121], CdSe quantum dot/rGO for energy harvesting [122] and Ni-graphene layers for corrosion resistant coatings [123].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples include the deposition of GO/chitosan films for drug release [53], CoFe 2 O 4 /rGO, Ni/GO and Sn nanoparticle/rGO films for energy storage [119][120][121], CdSe quantum dot/rGO for energy harvesting [122] and Ni-graphene layers for corrosion resistant coatings [123].…”
Section: +mentioning
confidence: 99%
“…This increase in surface area makes EPD-processed GRM surfaces a good substrate for the nucleation and growth of metal nanoparticles [70,123,136,139,152], and also allows a better utilisation of the GRM surface area for applications such as supercapacitor electrodes [34].…”
Section: Wrinkles Surface Roughness and Graphene Edgesmentioning
confidence: 99%
“…It is widely known that graphene possesses a large specific surface area and is easy to agglomerate. Previous reports already show that the use of NMP along with an ultrasonication process is effective to disperse graphene platelets, and GPLs would be randomly distributed and oriented in the Ni matrix. During the electroforming, a current density of 2 A dm −2 was used and a temperature of 40 °C and a pH of between 3 and 4 were maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Kyle et al studied the preparation of GPL/Ni composite coatings and the effect of GPLs on the hardness and corrosion resistance. They found that that GPL/Ni coatings have a much higher microhardness and better corrosion resistance than pure nickel coatings …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a single graphene layer considerably increases the corrosion resistance of such systems as copper / graphene [37] and nickel / graphene [38,39] and protects the surfaces of those metals from oxidation [40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%